1988
DOI: 10.1007/bf01939897
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of digoxin-like immunoreactivity and Na+,K+-ATPase inhibitory activity in rat plasma

Abstract: We measured endogenous digitalis-like factor (EDF) in rat plasma during acute saline infusion by two different procedures. Na+,K+-ATPase inhibitory activity in the rat plasma significantly increased during saline loading (7.8 +/- 2.2 vs 2.5 +/- 0.9%, with and without acute saline loading, respectively, p less than 0.05). On the other hand, the plasma digoxin-like immunoreactivity significantly decreased during acute saline loading (16.9 +/- 1.6 vs 32.0 +/- 2.8 pg digoxin equivalents/ml, with and without acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0
1

Year Published

1990
1990
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…The digi talis group of compounds usually has digoxin like immunoreactivity (26), but in the present experiment, the immunoreactivity to digoxin antibody of ouabain was significantly lower than that of digoxin, although those Na+,K+ ATPase inhibitory activities were not differ ent. These results may support the observation of Yamada et al (14) in which the Na+,K+ ATPase inhibitory activity dissociates from the digoxin-like immunoreactivity. Therefore, the possibility that endogenously synthesized oua bain is contained in the plasma extract still re mains.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The digi talis group of compounds usually has digoxin like immunoreactivity (26), but in the present experiment, the immunoreactivity to digoxin antibody of ouabain was significantly lower than that of digoxin, although those Na+,K+ ATPase inhibitory activities were not differ ent. These results may support the observation of Yamada et al (14) in which the Na+,K+ ATPase inhibitory activity dissociates from the digoxin-like immunoreactivity. Therefore, the possibility that endogenously synthesized oua bain is contained in the plasma extract still re mains.…”
Section: Discussionsupporting
confidence: 92%
“…One of the possible causes of the dif ference may be that the present plasma extract does not contain endogenously synthesized digoxin even if the substance is present in the plasma; that is, the substances determined are different. In addition, it has been reported that there are some digoxin-like immunoreac tive factors without Na+,K+-ATPase inhibitory activity (14,28). Another cause may be the dilution of the ouabain-like substance inhibit ing Na+,K±ATPase by the larger circulating blood volume in the NP group than in the N group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with our findings is problematic as Yamada et al studied much younger animals weighing about 130 g after 15 days of ACTH treatment, whereas we measured EDLF after 8 days of ACTH administration in rats weighing about 380 g. We hypothesize that the discrepancy in the results of these two experiments reflects a different time course of the changes in the two digitalis-like factors. Such dissociation between EDLF levels measured by different methods has been recently reported in volumeexpanded rats 30 and dogs, 31 and exemplifies the heterogeneity of EDLF.31 Moreover, sodium balance may be different on days 8 and 15 of ACTH treatment. In accord with previous findings, 1,2,23 plasma Na in ACTH-treated rats in our experiment was increased (indicating sodium retention), whereas no such difference was observed on day 15 of ACTH hypertension.…”
mentioning
confidence: 99%
“…Many steroids give false-pos itive results for digoxin, as do many lipids and bile acids. Recent findings indicate the dissociation of digoxin-like immunoreactivity from digitalis-like biological activity [3][4][5].We have recently purified to homogeneity two distinct digitalis-like factors from human urine based on [JH]ouabain displacing activity from intact human erythrocytes [6,7]. The polar compound was eluted off the C18 reverse phase column with 18% acetonitrile and cross-reacted very weakly with specific antidigoxin antibody.…”
mentioning
confidence: 99%